Investor Sentiment and Employment - Maurizio Montone; Remco C.J. Zwinkels (Tinbergen Institute, 2015)
We find that investor sentiment should affect a firm's employment policy in a world with moral hazard and noise traders. Consistent with the model's predictions, we show that higher sentiment among US investors leads to: (1) higher employment growth worldwide; (2) lower labor productivity, as the growth in employment is not matched by real value added growth; and (3) positive wage growth in countries with a greater proportion of high-skill labor, but negative wage growth otherwise. We also find evidence that sentiment induces greater labor instability during financial crises, which sheds new light on the view that financial development has a "dark side". Overall, the results suggest that sentiment has real effects, especially in countries that attract more foreign direct investments from the US and that are perceived as more popular among US investors.
Keywords: G10; G30; F21; J30; 330; Investor sentiment; labor market; financial development; financial crises